Reinforcement Learning Under Latent Dynamics: Toward Statistical and Algorithmic Modularity - Amortila, Philip; Foster, Dylan; Jiang, Nan; Krishnamurthy, Akshay; Mhammedi, Zakaria (NeurIPS 2024, 2024)
Real-world applications of reinforcement learning often involve environments where agents operate on complex, high-dimensional observations, but the underlying ("latent") dynamics are comparatively simple. However, beyond restrictive settings such as tabular latent dynamics, the fundamental statistical requirements and algorithmic principles for *reinforcement learning under latent dynamics* are poorly understood. This paper addresses the question of reinforcement learning under *general latent dynamics* from a statistical and algorithmic perspective. On the statistical side, our main negative result shows that *most* well-studied settings for reinforcement learning with function approximation become intractable when composed with rich observations; we complement this with a positive result, identifying *latent pushforward coverability* as a general condition that enables statistical tractability. Algorithmically, we develop provably efficient *observable-to-latent* reductions —that is, reductions that transform an arbitrary algorithm for the latent MDP into an algorithm that can operate on rich observations— in two settings: one where the agent has access to hindsight observations of the latent dynamics (Lee et al., 2023) and one where the agent can estimate *self-predictive* latent models (Schwarzer et al., 2020). Together, our results serve as a first step toward a unified statistical and algorithmic theory for reinforcement learning under latent dynamics.